2019
DOI: 10.1007/s40840-019-00833-6
|View full text |Cite
|
Sign up to set email alerts
|

Strong Geodetic Number of Complete Bipartite Graphs, Crown Graphs and Hypercubes

Abstract: The strong geodetic number, sg(G), of a graph G is the smallest number of vertices such that by fixing one geodesic between each pair of selected vertices, all vertices of the graph are covered. In this paper, the study of the strong geodetic number of complete bipartite graphs is continued. The formula for sg(K n,m ) is given, as well as a formula for the crown graphs S 0 n . Bounds on sg(Q n ) are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In the example above, we have already seen that X = {0, 6, 8} is an MGS of the graph in Figure 1. It is immediate to check that the paths induced by Arc[0, 6], Arc [6,8] and Arc [8,0] are geodesics. So X is also an MSGS of G.…”
Section: Lemma 8 ([18] Lemma 12)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the example above, we have already seen that X = {0, 6, 8} is an MGS of the graph in Figure 1. It is immediate to check that the paths induced by Arc[0, 6], Arc [6,8] and Arc [8,0] are geodesics. So X is also an MSGS of G.…”
Section: Lemma 8 ([18] Lemma 12)mentioning
confidence: 99%
“…In order to model a problem on social networks, a variant to the GNP has been introduced in [2] (see also [9,[11][12][13] and [8] where the state of the art on the strong geodetic number is summarized). Given a set S of supervisors of a social network, we suppose that these supervisors can communicate each other by using a single, fixed shortest path through the network.…”
Section: Introductionmentioning
confidence: 99%
“…The exact value of the strong geodetic number was computed for different families of graphs. For example, for complete bipartite graphs K n,m it was first computed for cases when n = m, and for n ≫ m in [4], and later in the general case in [1]. In [6], the strong geodetic number was computed for some balanced multipartite complete graphs and it was shown that computing the strong geodetic number of general complete multipartite graphs is NP-complete.…”
Section: Introductionmentioning
confidence: 99%
“…In [6], the strong geodetic number was computed for some balanced multipartite complete graphs and it was shown that computing the strong geodetic number of general complete multipartite graphs is NP-complete. The exact strong geodetic number was also computed for crown graphs S n 0 in [1], Hamming graphs K m K n in [5], Cartesian products K 1,n P l in [5], thin (n ≫ m) grids P n P m , and thin (n ≫ m) cylinders P n C m in [7], and i-level complete Appolonian networks A(i) in [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation